Microperimetry-Assessed Functional Alterations and OCT-Changes in Patients after Retinal Detachment Surgery Using Pars Plana Vitrectomy and SF6 Tamponade - María D. Díaz-Barreda; Isabel Bartolomé-Sesé; Ana Boned-Murillo; Antonio Ferreras; Elvira Orduna-Hospital; Francisco J. Ascaso; Isabel Pinilla (Diagnostics, 2021)
Background: We study the retinal function measured by macular integrity assessment microperimetry (MAIA) and structural changes assessed by scanning swept source optical coherence tomography (SS-OCT) between healthy individuals and patients undergoing pars plana vitrectomy (PPV) after rhegmatogenous retinal detachment (RRD). Methods: Cross-sectional study. Early Treatment Diabetic Retinopathy Study (ETDRS) grids were measured by SS-OCT and compared with the MAIA parameters. Results: Thirty-eight eyes with RRD (19 macula-on and 19 macula-off) were compared with 113 healthy eyes. The retinal sensitivity and average total threshold were reduced in all sectors in the RRD group; macular integrity index was increased. Macular thicknesses in total retina and ganglion cell layer (GCL)++ protocols were higher in the RRD group in nasal outer (NO) and central (C) sectors and only in C sector for GCL+ protocol. Thicknesses were lower in total retina, GCL++ protocols in the temporal outer (TO) sector and in the GCL+ protocol in NO sector. Best-corrected visual acuity (BCVA) correlated moderately with retinal sensitivity in all sectors and in just several sectors with time between the date of surgery and the test. The central nasal (CN) sector thickness and the average total threshold were higher in the macula-on subgroup. Conclusions: RRD and subsequent surgery results in functional and structural changes, especially in individuals with macular detachment.